Development of a silicon carbide ceramic based counter-flow heat exchanger by binder jetting and liquid silicon infiltration for concentrating solar power. Issue 16 (15th August 2022) - Thomas, Jonova; Banda, Mahesh; Du, Wenchao; Yu, Wenhua; Chuang, Andrew; France, David M.; Singh, Dileep
Abstract: A silicon carbide ceramic counter-flow heat exchanger with integrated headers was printed by binder jetting additive manufacturing process. Multiple phenolic binder infiltration cycles (3 or 5) followed by pyrolysis were conducted to increase the net carbon content of the printed SiC specimens. Subsequently, to attain full densification, silicon melt infiltration was used. The microstructure and mechanical properties were comprehensively characterized on the densified material. The chemical compositions and visual distribution of the various regions in the specimens were determined via scanning electron microscopy, while X-ray diffraction and synchrotron μ-computed tomography were used to provide a quantitative assessment of the volume fractions of the identified phase regions. Microhardness measurements showed dependence on the local microstructure. The fracture strength of the material was correlated with the specimen density and agreed with the reported values in the literature. High-temperature exposure at 750 °C for up to 200 h did not degrade the strength for the specimens with three phenolic-binder infiltrations; however, the strengths degraded for ones with five phenolic-binder infiltrations. The associated fracture toughnesses of the specimens were ∼3.4 MPam 1/2  at room temperature and 750 °C, and the thermal conductivities varied from >150 W/mK at room temperature to ∼45 W/mK at 750 °C. Hence, this study validated the use of the binder-jetting printed SiC ceramic materials for high-temperature heat exchanges. Finally, we also present in this work the first successful fabrication of a binder-jetting printed one-piece dense SiC ceramic heat exchanger body with unblocked channels that can be used for the flow of heat transfer fluids.